Revista de Economía & Administración Julio - Diciembre de 2020 - Vera-Ramírez , Henry Daniel; Torres-Medina, Fernando; Márquez, Fredy José; Duque Sandoval, Henry; Garizado-Román, Paula Andrea (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2021)
Número completo